IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH DALAM MENINGKATKAN KINERJA GURU: STUDI KASUS DI SMAN 112 JAKARTA BARAT - Wasliman, Iim; Khori, Ahmad; Sauri, Supyan; Juwarto, Juwarto; Haryono, Wasis; Yusuf, Yusuf; Sartono, Sartono (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2025)
This study analyzes the implementation of School-Based Management (SBM) and its impact on teacher performance at SMAN 112 West Jakarta. SBM, as a school autonomy strategy, aims to improve the overall quality of education, including teacher performance, which is crucial for successful learning. Although the government supports SBM through various regulations, its implementation often faces challenges like inconsistent understanding and limited resources. Using a qualitative approach with a case study method, this research gathered data through in-depth interviews with the principal, vice principals, teachers, and school committee representatives, as well as observations and document analysis. The findings indicate that SMAN 112 West Jakarta has implemented SBM with varying degrees of autonomy, involving stakeholders in strategic decision-making, and practicing transparency and accountability. The principal's transformational leadership and planned resource management also contribute. SBM has proven to have a significant positive impact on teacher motivation and performance, primarily through the autonomy and participation that foster creativity, innovation, and professional development. The school committee plays an active role in providing facility and training support. However, challenges such as resource limitations and parent participation still exist. Recommendations include improving communication, training, and partnerships for the continuous optimization of SBM to enhance teacher performance and educational quality. ABSTRAKPenelitian ini menganalisis implementasi Manajemen Berbasis Sekolah (MBS) dan dampaknya terhadap kinerja guru di SMAN 112 Jakarta Barat. MBS, sebagai strategi otonomi sekolah, bertujuan meningkatkan mutu pendidikan secara menyeluruh, termasuk kinerja guru yang krusial bagi keberhasilan pembelajaran. Meskipun pemerintah telah mendukung MBS melalui berbagai regulasi, implementasinya sering menghadapi kendala seperti kurangnya pemahaman merata dan keterbatasan sumber daya. Menggunakan pendekatan kualitatif dengan metode studi kasus, penelitian ini mengumpulkan data melalui wawancara mendalam dengan kepala sekolah, wakil kepala sekolah, guru, dan komite sekolah, serta observasi dan analisis dokumen. Hasil penelitian menunjukkan bahwa SMAN 112 Jakarta Barat telah menerapkan MBS dengan tingkat otonomi bervariasi, melibatkan stakeholder dalam pengambilan keputusan strategis, dan mempraktikkan transparansi serta akuntabilitas. Kepemimpinan transformasional kepala sekolah dan pengelolaan sumber daya yang terencana turut mendukung. MBS terbukti berdampak positif signifikan pada motivasi dan kinerja guru, terutama melalui otonomi dan partisipasi yang mendorong kreativitas, inovasi, dan pengembangan profesional. Komite sekolah berperan aktif memberikan dukungan fasilitas dan pelatihan. Namun, tantangan berupa keterbatasan sumber daya dan partisipasi orang tua masih ada. Rekomendasi meliputi peningkatan komunikasi, pelatihan, dan kemitraan untuk optimalisasi MBS berkelanjutan demi peningkatan kinerja guru dan kualitas pendidikan.